2014
DOI: 10.1242/jcs.138537
|View full text |Cite
|
Sign up to set email alerts
|

The SMN Tudor SIM-like domain is key to SmD1 and coilin interactions and to Cajal body biogenesis

Abstract: Cajal bodies (CBs) are nuclear organelles involved in the maturation of spliceosomal small nuclear ribonucleoproteins (snRNPs). They concentrate coilin, snRNPs and the survival motor neuron protein (SMN). Dysfunction of CB assembly occurs in spinal muscular atrophy (SMA). Here, we demonstrate that SMN is a SUMO1 target that has a small ubiquitin-related modifier (SUMO)-interacting motif (SIM)-like motif in the Tudor domain. The expression of SIM-like mutant constructs abolishes the interaction of SMN with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The critical function that is affected in SMA is snRNP assembly, and it is well known that the snRNP biogenesis pathway involves four steps: (A) SMN oligomerization [22], (B) SMN interaction with Gemin proteins [27], (C) SMN binding to the Sm proteins of snRNPs, which are key constituents of spliceosomes [15], (D) SMN-coilin interaction in Cajal bodies [5], the nuclear organelles involved in the maturation of spliceosomal snRNPs.…”
Section: Resultsmentioning
confidence: 99%
“…The critical function that is affected in SMA is snRNP assembly, and it is well known that the snRNP biogenesis pathway involves four steps: (A) SMN oligomerization [22], (B) SMN interaction with Gemin proteins [27], (C) SMN binding to the Sm proteins of snRNPs, which are key constituents of spliceosomes [15], (D) SMN-coilin interaction in Cajal bodies [5], the nuclear organelles involved in the maturation of spliceosomal snRNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that SMN is modified by SUMO1 at residue K119. 62 Sumoylated SMN is not enriched in the CB, which contains the desumoylation enzyme USPL1. This suggests that desumoylation of SMN takes place in the CB.…”
Section: How Does Modification Impact Smn's Cb Activity?mentioning
confidence: 97%
“…[91][92][93][94][95] In addition to overall protein levels, post-translational modifications (PTMs) of resident proteins, including SMN and coilin, are almost certainly important for establishing and maintaining inter-and intra-molecular interactions within Cajal bodies. [96][97][98][99][100] Disruption of these PTMs can result in mislocalization of SMN and alterations in Cajal body integrity. These and other factors will need to be addressed by future studies.…”
Section: Inter-and Intra-molecular Interactions Within the Cajal Bodymentioning
confidence: 99%